Adsorption Characteristics of Heavy Metals on to Recycled Vehicular Tire Activated Carbon as Potential Adsorbent with Phosphoric Acid - Tamatheir S. Musa (Journal of Global Pharma Technology, 2018)
Heavy metals considered poisonousness to plants and microorganisms in the earth and environmentally friendly contamination. The objective of the work is to transform vehicular tires, a greatly existing unwanted substance by treating with H3PO4 with and without treatment at 900°C as a chemical agent into profitable adsorbent for the expulsion of Cu+2, Zn+2 and Pb+2ions. In this work, removal of Cu+2, Zn+2 and Pb+2ions by utilizing VTAC and the influence of different factors such as contact time, pH, adsorbent quantity, metal concentration and temperature on the adsorption have been calculated where the maximum adsorption of Cu+2 ,Zn+2 and Pb+2 was 99.994, 99.5667 and 96.3974, respectively for ACs which was treated with H3PO4 with treatment at 9000C and the equilibrium time was 72 hours and temperature of 30 0C, PH 3, adsorbent dosage 5 mg/L and initial concentration 30 mg/L. The isotherm models that studied Langmuir and Freundlich and present Freundlich more suitable due to have high value correlation coefficient (R2) and pseudo-first order and pseudo- second order kinetics also studied where pseudo-first order more suitable to describe the adsorption properties of VTAC as applied mechanism of Intraparticle diffusion model that appeared desirable results.Keywords: Activated carbon, Vehicular tire, Adsorption, Heavy metal ions.